Comparison of catheter-directed thrombolysis and anticoagulation in intermediate-risk pulmonary embolism: A retrospective analysis - Özden Omaygenç, Derya; Omaygenç, Mehmet Onur (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND AND OBJECTIVES: The selection of escalation of care strategies for the treatment of intermediate-risk pulmonary embolism (PE) is a matter of debate. Here, we aimed to assess the features of our population treated either with anticoagulation (AC) alone or catheter-directed thrombolysis (CDT). We also sought to identify a relationship between high residual systolic pulmonary artery pressure (sPAP) and demographic and clinical variables. PATIENTS AND METHODS: The retrospective data of 30 intermediate-high-risk PE patients were analyzed. CDT was used in 14 (46.7%) cases. Enoxaparin (b. i. d) injections were administered in the AC group. In the CDT group, patients received 5 mg bolus dose of alteplase followed by 1 mg/h infusion for 24 h. Estimated sPAP at presentation and discharge was recorded. A value equal to or greater than 40 mmHg in the latter was accepted as a significant rise. RESULTS: The patients in the CDT group had a lower HAS-BLED score (2 [0-3] vs. 1 [0-3], P = 0.03). Although initial sPAP values were comparable among treatment arms, sPAP at discharge was significantly lower in the CDT group (mmHg, 42 +/- 11.2 vs. 33.6 +/- 9.7, P = 0.04). The reduction in sPAP at discharge was also significantly higher in this group. The degree of reduction in sPAP was considerably correlated with baseline sPAP (r: 63.2, P < 0.001). Finally, the baseline sPAP measurement and HAS-BLED score of the patients with high residual sPAP were significantly higher (56.6 +/- 13.1 vs. 67.3 +/- 11.3, P = 0.02, and 1 [0-3] vs. 2 [0-3], P = 0.02, respectively). CONCLUSION: CDT was preferred over AC when lower bleeding risk was anticipated for intermediate-high-risk PE patients in our sample population. Eventually, CDT provided lower discharge sPAP levels and a greater reduction in sPAP. However, the factors associated with high sPAP at discharge were only high baseline sPAP measurement and HAS-BLED score.
Keywords: Anticoagulants; Pulmonary Embolism; Pulmonary Hypertension; Thrombolytic Therapy